Prevalence of antibodies against BKPyV subtype I and IV in kidney transplant recipients and in the general Czech population - Hejtmánková, Alžběta; Roubalová, Kateřina; Forejtová, Alena; Žáčková Suchanová, Jiřina; Forstová, Jitka; Viklický, Ondřej; Španielová, Hana (Journal of medical virology, 2019)
Active infection with BK polyomavirus (BKPyV) may cause serious complications in transplantation settings. Recently, the level of BKPyV IgG seroreactivity in graft donors has been shown to predict viremia and BKPyV-associated nephropathy in kidney transplant (KTx) recipients. Pretransplantation testing of the donor and recipient BKPyV serostatus could, therefore, identify patients at high risk. For the development of serological immunoassays, antibody response to the predominant BKPyV subtypes (BKPyV-I and BKPyV-IV) was studied using virus-like particle (VLP)-based enzyme-linked immunosorbent assay (ELISA). VLPs made from the capsid protein, VP1, derived from BKPyV-I and BKPyV-IV subtypes were produced using a baculovirus expression system and used as antigens. The tests were used for IgG antibody determination in 50 KTx recipients and 111 healthy blood donors. While 87% of samples reacted with mixed BKPyV-I and BKPyV-IV antigens, only 49% of samples were reactive in both ELISA tests when using BKPyV-I or BKPyV-IV antigens separately. Twenty-seven percent of healthy blood donors and 26% of KTx recipients were reactive only with BKPyV-I, while 9% and 20% were reactive only with BKPyV-IV, respectively. To determine the specificities of the antigens, selected seropositive samples were retested after preadsorption with soluble BKPyV-I, BKPyV-IV, or JC polyomavirus antigens. The experiments confirmed that recombinant VP1 VLP-based ELISAs predominantly detected BKPyV type-specific antibodies. The results imply that anti-BKPyV antibody ELISA tests should contain a mixture of subtype-specific VLP-based antigens instead of antigen derived from the most prevalent BKPyV-I subtype. The tests can be used for serological surveys of BKPyV infection and improved KTx patient management.
Keywords: Polyomavirus Infections; příjemce transplantátu; virus BK; Immunoglobulin G; protilátky virové; Seroepidemiologic Studies; séroepidemiologické studie; Česká republika; polyomavirus BK; transplantation; virus-like particle (VLP)-based enzyme-linked immunosorbent assay (ELISA); BK Virus; cross-reactivity; Transplant Recipients; imunoglobulin G; polyomavirus JC; ELISA; Czech Republic; Enzyme-Linked Immunosorbent Assay; lidé; polyomavirové infekce; Kidney Transplantation; transplantace ledvin; Humans; Antibodies, Viral; transplant patient management